2022
DOI: 10.3390/ijms232113574
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Gut Microbiota in Memory Impairment and Alzheimer’s Disease via the Inhibition of the Parasympathetic Nervous System

Abstract: The gut microbiota has been demonstrated to play a critical role in maintaining cognitive function via the gut-brain axis, which may be related to the parasympathetic nervous system (PNS). However, the exact mechanism remains to be determined. We investigated that patients with mild cognitive impairment (MCI) and Alzheimer’s disease (AD) could exhibit an altered gut microbiota through the suppression of the PNS, compared to the healthy individuals, using the combined gut microbiota data from previous human stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…In our study, family Desulfovibrionaceae as well as order Desulfovibrionales were significantly and causally associated with increased risk of AD, and previous clinical studies have corroborated our findings. The study by Hou et al ( 45 ) found higher abundance of family Desulfovibrionaceae and order Desulfovibrionales in AD patients, the same results were found in patients with cognitive impairment in the study by Park et al ( 46 ). Haran et al ( 47 ) combined with machine learning found that a representative species of the sulfate-reducing Desulfovibrio genus (D. fairfieldensis) could serve as a highly significant predictor of AD.…”
Section: Discussionmentioning
confidence: 54%
“…In our study, family Desulfovibrionaceae as well as order Desulfovibrionales were significantly and causally associated with increased risk of AD, and previous clinical studies have corroborated our findings. The study by Hou et al ( 45 ) found higher abundance of family Desulfovibrionaceae and order Desulfovibrionales in AD patients, the same results were found in patients with cognitive impairment in the study by Park et al ( 46 ). Haran et al ( 47 ) combined with machine learning found that a representative species of the sulfate-reducing Desulfovibrio genus (D. fairfieldensis) could serve as a highly significant predictor of AD.…”
Section: Discussionmentioning
confidence: 54%
“…Escherichia fergusonii , a gram-negative bacterium belonging to the genus Escherichia of the family Enterobacteriaceae, is an emerging pathogen with zoonotic potential. Escherichia fergusonii has been isolated from patients with wound infections, urinary tract infections, inflammatory bowel disease, ischemic bowel disease, pancreatic cancer, and Alzheimer's disease; however, its virulence determinants are not well understood[ 9 - 12 ]. Romboutsia timonensis is a pathogenic bacterium first reported in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…The eXtreme Gradient Boosting (XGBoost) machine learning method, a widely utilized gradient boosting algorithm, was chosen for its capability to refine the microbial candidates potentially contributing to MAFLD risk. To interpret the outcomes of the XGBoost model, we applied the Shapley Additive exPlanations (SHAP) method and utilized the SHAP package (version 0.39.0) to compute the average absolute SHAP values for each variable [56]. This process allowed us to observe the importance and impact of individual variables on the classification.…”
Section: Core Microbial Biomarker and Enterotype Analysismentioning
confidence: 99%